Effect of Intravenous Fentanyl to Prevent Radial Artery Spasm During Trans Radial Intervention - Saha, Partha Pratim; Choudhury, Amal Kumar; Ahsan, Syed Ali; Momen, Abdul; Patwary, Shafiqur Rahman; Alam, Nur; Uddin, Kofil; Sarkar, Pritha; Amin, Heru Al (University Heart Journal, 2022)
Background: Radial artery spasm (RAS), one of the commonest complications in trans radial cardiac intervention, leads a variety range of adverse events. Different prevention strategies had been introduced and the use of sedation is one of them. Use of Fentanyl is common in cardiac interventions to achieve sedation and analgesia and also offers a potent vasodilatory effect. Objective: This study aimed to explore the role of fentanyl in the prevention of RAS in trans radial intervention. Methods: This observational analytic study was conducted in National Institute of Cardiovascular Diseases (NICVD) for a period of 1 year following approval of the protocol in the total of 260 patients who underwent coronary intervention through trans radial approach (Coronary Angiogram and or Percutaneous Coronary Intervention). They were categorized in 2 group- group I patients received intravenous fentanyl and group II patients didn’t receive fentanyl. Besides this, each patient received all treatments according to standard protocol of NICVD. RAS was identified by subjective and objective evidence. Patient is discomfort was quantified with a visual analogue scale. Results: The frequency of RAS was 17.70% in group I versus 30.80% in group II (p =0.014). Intravenous use of fentanyl significantly reduced radial artery spasm (p< 0.05). Bivariate logistic regression analysis showed use of fentanyl had lower odds to prevent radial artery spasm (odds ratio [OR]: 0.430, 95% confidence interval [CI]: 0.239 to 0.779). The number needed to treat to avoid 1 case of spasm was 8. Multivariate logistic regression analysis also revealed use of fentanyl was the strong predictor of RAS ([OR]: 0.370; 95% [CI]: .195-.703) as well as use of reprocessed sheath, smoking, catheter diameter 6Fr and visual analogue scale (VAS) Score during cannulation became independent predictaor of RAS. Patient discomfort in VAS score was 4.75±2.70 in Group I versus 5.33±2.64 in group II (p< 0 .05). Conclusion: In this study, use of fentanyl reduced the frequency of radial artery spasm and the procedure related level of patient discomfort. University Heart Journal 2022; 18(1): 54-60